1991
DOI: 10.1346/ccmn.1991.0390608
|View full text |Cite
|
Sign up to set email alerts
|

Chlorite Vermiculitization and Pyroxene Etching in an Aeolian Periglacial Sand Dune, Allen County, Indiana

Abstract: Abstract--Weathering has etched and deeply-dentieulated the constituent orthopyroxenes, and chlorite has been transformed to vermiculite in the upper 3 m of an aeolian, periglacial sand dune formed in northeastern Indiana about 13,000 b.p. Pyroxene weathering begins with the development of cleavageparallel etch pits on {010} and ( 100 } surfaces. These pits coalesce and eventually crop out on basal surfaces as denticulations. The mean denticulation size increases logarithmically toward the surface, and the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…Negligible expansion as indicated by the basal spacings at 9.4 and 14 ]1 with ethylene glycol and glycerol, incomplete contraction on heating, expansion and/or an increase in intensity of basal spacings of (002) and (004) by glycerol solvation following Mg-saturation, and contraction on heating at 550~ following K-saturation in these samples are consistent with the hydroxy-Al interlayer in the two-layer hydrate and dehydrated types of vermiculite (April and Newton, 1983;Buurman et al, 1988;Barnhisel and Bertsch, 1989;Douglas, 1989;Argast, 1991).…”
Section: X-ray Diffraction Analysissupporting
confidence: 54%
“…Negligible expansion as indicated by the basal spacings at 9.4 and 14 ]1 with ethylene glycol and glycerol, incomplete contraction on heating, expansion and/or an increase in intensity of basal spacings of (002) and (004) by glycerol solvation following Mg-saturation, and contraction on heating at 550~ following K-saturation in these samples are consistent with the hydroxy-Al interlayer in the two-layer hydrate and dehydrated types of vermiculite (April and Newton, 1983;Buurman et al, 1988;Barnhisel and Bertsch, 1989;Douglas, 1989;Argast, 1991).…”
Section: X-ray Diffraction Analysissupporting
confidence: 54%
“…Pyroxene crystals were moderately to strongly weathered, with a typical linear parallel pattern and/or elongated etch pits aligned along the longer crystallographic axis and the cleavage planes, and showed peculiar denticulated (multi-needle) margins on the basal faces (e.g. Argast, 1991;Velbel and Losiak, 2010). Due to the small size of pyroxene crystals and to their state of weathering, it was only possible to obtain reliable analysis for the minerals of SPI and TAU (Table 6a).…”
Section: Scanning Electron Microscopy (Sem/eds)mentioning
confidence: 99%
“…However, not all pyriboles weather to clay minerals by topotactic transformation. A number of studies have shown that weathering of hornblende may proceed by congruent dissolution along crystallographic directions and precipitation of clay minerals and iron oxides from solution with no crystallographic relationship persisting between hornblende and clay minerals (Berner and Schott, 1982;Anand and Gilkes, 1984;Velbel, 1989, Argast, 1991. Topotaxial transformation of pyriboles to layer silicates is presumably facilitated if minimum adjustments in structure and composition are involved (Gilkes et aL, 1986).…”
Section: Introductionmentioning
confidence: 99%